Coding template of sensorless sun tracking using azimuth-elevation mode - Idris, Norain; Zakaria, Muhammad Zulfattah; Ahmad, Emy Zairah; Mohd Yassim, Halyani; Hussin, Mohamed Saiful Firdaus (Penerbit UTM Press, 2015)
The next explosion in solar power research was in 1997 as consequence to Kyoto Protocol. This protocol outlined the effect of greenhouse emission which endangers our Earth. As the result, research in solar power field started to take its path again. This work is a part of the UTeM project to build the first CST model in South East Asia and was aimed to develop an azimuth-elevationmode-based template using MATLAB programming for the calculation of the heliostat position with respect to the heat absorber mounted at the top of the CST. This template will serve as the calculation platform to control the movement of the heliostat using a two-axis motion system so that the sun light will be redirected perfectly to the absorber all day long. Since the heliostat normal vector depends on sun position vector, both vectors were calculated by the program and were set as the output of the program. The input from the user will be the Cartesian coordinate of the heliostat and absorber by taking the absorber tower frontal surface and its base as the origin and also the date. The result will be in vector form and will change automatically according to the Sun movement. These values will be programmed in the micro controller which will control the motion system of the heliostat, which will be done by the Control Department of UTeM. The program´s functionality was proved via several verifications and its accuracy which is 0.0005 as stated and verified via comparison with analytical calculations. From the verifications, it can be seen that difference of the numerical and analytical results varied from 0.0000 to 0.0005 which validates the statement of minimum accuracy of the numerical calculated results is 5/10,000.